STUDI FOTOLUMINESENSI PADA LAPISAN TIPIS - Dwikoranto, ; Munasir, (Matematika dan Sains, 2010)
It had been grown a thin layer of gallium nitride (GaN) above the substrate sapphire (0001) using unbalanced method DC magnetron sputtering.@Deposition temperature were varied between 630-740 oC.@Study of optical properties of the layers GaN thin measurements was done using fotoluminesensi (PL) at room temperature.@The results of PL measurements showed that the intensity of PL spectrum of the higher by raising the temperature of deposition, which means quality optical properties of GaN thin layers the better. GaN thin layers grown has the optical band gap of ~ 3.4 eV and luminesensi dominant place in the blue region (~2.7eV).@Layer thin GaN has a FWHM ~ 0.421eV for the temperature deposition temperature of 740 oC deposition.oC.@Study of optical properties of the layers GaN thin measurements was done using fotoluminesensi (PL) at room temperature.@The results of PL measurements showed that the intensity of PL spectrum of the higher by raising the temperature of deposition, which means quality optical properties of GaN thin layers the better. GaN thin layers grown has the optical band gap of ~ 3.4 eV and luminesensi dominant place in the blue region (~2.7eV).@Layer thin GaN has a FWHM ~ 0.421eV for the temperature deposition temperature of 740 oC deposition.